Improved anaerobic digestion performance of Miscanthus floridulus by different pretreatment methods and preliminary economic analysis. (1st March 2018) - Fu, Shan-Fei; Chen, Kai-Qiang; Zhu, Rong; Sun, Wen-Xin; Zou, Hua; Guo, Rong-Bo
Highlights: Improved AD performance by pretreatment and economic analysis were conducted. Pretreatments improved AD performance significantly. Different pretreatments have unequal effects on the structure of Miscanthus. Microaerobic pretreatment is both economically feasible and environmental friendly. Abstract: During the anaerobic digestion (AD) of cellulosic substrate, an economical and environmental friendly pretreatment method should be selected to improve the AD performance. In this study, five pretreatment methods include four traditional pretreatment methods (alkali hydrogen peroxide pretreatment, NaOH pretreatment, HCl pretreatment and hot water pretreatment) and one new developed pretreatment (microaerobic pretreatment) method were selected to study the effects of pretreatment on the AD of Miscanthus floridulus . In addition, preliminary economic analysis of different pretreatment methods was also conducted. Results showed pretreatment could significantly improve the AD performance of Miscanthus . After alkali hydrogen peroxide pretreatment, microaerobic pretreatment, NaOH pretreatment, HCl pretreatment and hot water pretreatment the methane yields of Miscanthus were 41.1%, 25.5%, 18.7%, 15.7% and 10.2% higher than that of untreated sample. Though all these five pretreatment methods could improve the methane yield significantly, their action sites were different. H2 O2 pretreatment and NaOH pretreatment were efficient in removal lignin from Miscanthus floridulus . Hemicellulose structure was also partly destroyed during H2 O2 pretreatment and NaOH pretreatment. HCl pretreatment was efficient in destruction of hemicelluloses structure and partly destroyed the cellulose structure. Microaerobic pretreatment and hot water pretreatment were mainly acted in partly destruction of hemicelluloses and cellulose components. Preliminary economic analysis showed compared with un-pretreated group only microaerobic pretreatment was economically feasible. In addition, compared with other pretreatment methods, microaerobic pretreatment just needs limited amount of oxygen, which is more environmental friendly.